Effect of Vojta Therapy on Balance and Walking of Community Dwelling Chronic Stroke Patients - W, Tayati; N, Chompunuch; P, Wongphaet (ASEAN Journal of Rehabilitation Medicine, 2020)
Objectives: To evaluate effect of Vojta Therapy on balance and walking of community dwelling chronic stroke patients. Study design: Single group clinical trial with pre and post test. Setting: VojtaTherapy clinic, Division of Physical Therapy, Department of Rehabilitation Medicine, Trang Hospital. Subjects: Community dwelling chronic stroke patients with abnormal gait referred to the VojtaTherapy clinic. Methods: Every participant did a timed up and go test (TUGT) immediately before and after the VojtaTherapy. Techniques were chosen according to response of patients with 30 minutes per session. Treatment and assessment were repeated once a week for three weeks. Results: Twenty chronic stroke patients with average age of 63.1 (SD = 13.23) years and average duration after stroke of 58.35 (SD = 52.83) months were enrolled into the study. The median TUGT scores of the first, second and third pre-treatment were 28, 22 and 19.5 respectively. Friedman test demonstrated a significant difference (p < 0.001). Median TUGT Score of the first, second, and third post treatment TUGT score were 22.5, 18 and 18.5 respectively. Wilcoxon test showed significant difference of pre versus post treatments in everysessions (p < 0.0001). Conclusion: Once a week of VojtaTherapy for three weeks can improve walking in community dwelling chronic stroke patients.